Pengaruh Model Pembelajaran Contextual Teaching Learning (CTL) Terhadap Hasil Belajar Siswa Pada Tema 8 Subtema 1 kelas V di SDN Alas Rajah 3 Bangkalan - Andika Adinanda Siswoyo; Yusak, Rizal (Universitas Negeri Surabaya, 2025)
The purpose of this study was to determine whether there was any influence of the contextual teaching and learning model on student learning outcomes in the 8 sub-themes 1 class v theme at SDN Alas Rajah 3 Bangkalan and to find out how students responded to learning using the contextual teaching and learning model. This study used a quantitative method with a pre-experimental research design with the type of one group pretest posttest design. The research population is all fifthgrade students at SDN Alas Rajah 3 Bangkalan for the 2022/2023 academic year. Sampling using nonprobability sampling technique with saturated sampling type. The research sample was 15 students. Data collection techniques in this study used test questions, observation, and questionnaires. The results of the study show: 1) there is an influence of the contextual teaching and learning model on student learning outcomes in the theme 8 sub-theme 1 class v at SDN Alas Rajah 3 Bangkalan. This can be known through the results of the Wilcoxon test obtained Significance (2-tailed) 0.01 <alpha 0.05. 2). Student responses to learning can be identified through questionnaires which are carried out when students have finished carrying out learning activities. The results of the student response questionnaire sheet for learning got an average percentage of 84% in the very good category. So that it can be said that the student's response to learning using the contextual teaching and learning model is very good.